Pengaruh Sudut Bukaan Heksagonal Terhadap Kapasitas Geser Castellated Steel Beam - Ida Barkiah; Arya Rizki Darmawan; Muhammad Fitrah Dzikry (Jurnal Teknologi Berkelanjutan, 2021)
The opening in the castellated steel beam body affects the increase in the flexural capacity and the shear capacity of the steel beam. The research was conducted by determining the span of elements of conventional steel beams and castellated steel beams which have the same length. Steel beams are subjected to two concentrated loads at two points in 1/3 of the span. This study concludes that the effect of the geometric opening on the castellated steel beam will decrease the shear capacity. At the hexagonal opening angle of 45°-50° there is a decrease in shear capacity of about 18%. The optimum shear capacity value occurs at an opening angle of 20° with a decrease in shear capacity of 3%. The failure pattern that occurs is diagonal buckling (buckling due to shear) of the body at 1/3 of the span.